2022
DOI: 10.3390/cancers14040915
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2 Trial (POLA Study) of Lurbinectedin plus Olaparib in Patients with Advanced Solid Tumors: Results of Efficacy, Tolerability, and the Translational Study

Abstract: We hypothesized that the combination of olaparib and lurbinectedin maximizes DNA damage, thus increasing its efficacy. The POLA phase 1 trial established the recommended phase 2 dose of lurbinectedin as being 1.5 mg (day 1) and that of olaparib as being 250 mg/12 h (days 1–5) for a 21-day cycle. In phase 2, we explore the efficacy of the combination in terms of clinical response and its correlation with mutations in the HRR genes and the genomic instability (GI) parameters. Results: A total of 73 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…LUR has been evaluated in combination with ICIs (anti-PD-L1 and anti-CTLA-4 [ 152 ]) and in combination with irinotecan [ 153 , 154 ], ATR [ 122 , 155 ] alone or combined with ATM [ 156 ] and PARP [ 157 ] inhibitors, anti-VEGF [ 158 ] combined with cisplatin [ 83 , 159 , 160 ], paclitaxel [ 158 ], gemcitabine [ 161 ], capecitabine [ 162 ], doxorubicin [ 41 , 163 , 164 ], and immunomodulatory biomolecules such as antibody-drug complexes commonly referred to as ADCs (4C9-DM1 that targets c-Kit [ 165 ]).…”
Section: Combination Therapies Involving Trabectedin and Lurbinectedinmentioning
confidence: 99%
See 3 more Smart Citations
“…LUR has been evaluated in combination with ICIs (anti-PD-L1 and anti-CTLA-4 [ 152 ]) and in combination with irinotecan [ 153 , 154 ], ATR [ 122 , 155 ] alone or combined with ATM [ 156 ] and PARP [ 157 ] inhibitors, anti-VEGF [ 158 ] combined with cisplatin [ 83 , 159 , 160 ], paclitaxel [ 158 ], gemcitabine [ 161 ], capecitabine [ 162 ], doxorubicin [ 41 , 163 , 164 ], and immunomodulatory biomolecules such as antibody-drug complexes commonly referred to as ADCs (4C9-DM1 that targets c-Kit [ 165 ]).…”
Section: Combination Therapies Involving Trabectedin and Lurbinectedinmentioning
confidence: 99%
“…LUR has been combined with irinotecan in ovarian cell clear carcinoma cell lines showing synergistic effects [ 154 ] and in a case report showing BRCA-mutated platinum-resistant ovarian cancer patients had exceptional clinical responses [ 153 ]. LUR + olaparib (PARP inhibitor), in a phase I clinical trial for advanced solid tumours, is feasible and exhibited a disease control rate of 72.6% [ 157 ]. LUR + doxorubicin improved safety in a phase III clinical trial of SCLC [ 164 ], and in a phase II clinical trial, a benefit was observed in several types of metastatic and unresectable sarcomas [ 41 ].…”
Section: Combination Therapies Involving Trabectedin and Lurbinectedinmentioning
confidence: 99%
See 2 more Smart Citations
“…None of the patients achieved an objective response, but 60% of these obtained disease stabilization. In the subsequent phase II POLA trial, the combination of lurbinectedin 1.5/m 2 on day 1 + olaparib 250 mg BID on days 1–5 3qwk was administered to heavily pretreated patients with high-grade ovarian cancer, endometrial cancer, and triple-negative breast cancer ( 30 ). There was a trend to a better overall response rate in the patients with endometrial cancer than in those with ovarian cancer ( p = 0.057) ( Table 2 ).…”
Section: Antineoplastic Activity Of Lurbinectedin: In Vitro...mentioning
confidence: 99%